EVALUATING AND IMPLEMENTING BUSINESS MODEL BASED ON BPEL STRUCTURE: ASYSTEMATIC LITERATURE REVIEW - Nenden Eva Meilani Herlina; Sayyid Taufiq Abdulhafizh; Ihfan Aditya Ghafur; RD. Rohmat Saedudin (SITEKNIK: Sistem Informasi, Teknik dan Teknologi Terapan, 2024)
In an increasingly dynamic business world, the ability to adapt and innovate is the key to success. Flexible and efficient business models play an important role in this. Business Process Execution Language (BPEL) as an XML-based business process execution standard offers a solution to design, develop, and implement business models efficiently, effectively, and standardized. This study explores how BPEL can be used to evaluate and implement business models. It begins with a brief explanation of the concepts of business models, BPM, and BPEL. This study uses literature analysis, case studies, and conceptual model development. First, we conduct an in-depth review of the literature related to BPEL, business models, and related practices. Then, through case studies in several organizations, we evaluate the effectiveness of BPEL implementation in improving business processes and related business models. The results of the study show that the implementation of BPEL-based business models can increase the flexibility and responsiveness of organizations to market changes. These advantages are especially evident in increasing process efficiency, reducing operational costs, and improving the quality of service to customers.